THE ROLE OF THE POLICE IN ERADICATING ILLEGAL LEVIES IN THE ISSUANCE OF DRIVER'S LICENSES IN THE JURISDICTION OF THE MEDAN POLICE - Andi Muhammad Arif Pulungan; Mustamam Mustamam; Cut Nurita (Jurnal Ilmiah METADATA, 2026)
Illegal levies are criminal acts regulated in various legal provisions, especially related to corruption and extortion. Based on the results of the study, it is known that law enforcement against illegal levy perpetrators in the issuance of Driver's Licenses in the jurisdiction of the Medan Police involves various efforts, ranging from prevention to enforcement. Preventive efforts such as the inclusion of anti-pungli pledges, strict supervision, and the development of a code of ethics are very important. In addition, strict action against the perpetrators of fraud, including police members, is also needed. The public can also play a role in reporting pungli through the application. Obstacles to overcoming illegal levies in the issuance of driver's licenses in the jurisdiction of the Medan Police are the lack of public awareness, difficult proof, and lack of public participation in reporting pungli. Efforts to counter it include prevention through education and socialization, strengthening the role of the Saber Pungli Task Force, and strict law enforcement.